Multidrug-resistant Klebsiella pneumoniae and Klebsiella variicola isolated from patients in Portuguese hospitals: Genomic and phenotypic characterization - Joana Castro; Daniela Araújo; Hugo Oliveira; Liliana Fernandes; Ricardo Oliveira; Erick Brinks; Gyu-Sung Cho; Charles Franz; Maria José Saavedra; Sónia Silva; Carina Almeida (The Microbe)
The emergence of antibiotic-resistant Klebsiella spp. has become a huge problem in clinical settings. In this study, we aimed to characterize the molecular and phenotypic features of 21 MDR Klebsiella isolates (n = 19 of K. pneumoniae, and n = 2 of K. variicola) isolated from patients admitted to two central hospitals in northern Portugal by using whole-genome sequencing (WGS), followed by an in vitro assessment of biofilm formation and in vivo evaluation of the pathogenicity in a Galleria mellonella larval model. Our findings showed a high prevalence of O1/O2 serotypes (14/21; 67 %) among the isolates tested, which is consistent with previous reports from Portugal. In contrast, a wide variety of K locus serotypes was found, where ST15-KL19 (4/21; 19 %) associated to serotype O1/O2v2 was the dominant one. Within the O1/O2v2 serotype, a ST10-KL151 Klebsiella variicola (strain H97) harboured a high number of virulence genes. We also found statistical differences in the ability to produce biofilm biomass within the strains, with a ST280-KL23 K. pneumoniae outcompeting nine other strains. According to our results, the most prominent serotype able to cause the death of G. mellonella was the KL105-O1/O2v2. Our findings emphasized the importance of the conducting continuous molecular surveillance in order to reveal the key molecular features to be considered in the development of novel strategies to treat Klebsiella spp.-associated infections.